Protective Effect of Thalidomide on 2,4,6-Trinitrobenzenesulfonic Acid-Induced Experimental Colitis in Rats via the Inhibition of T Helper 17 Cells - Ying Xie; Dandan Li; Xiaoshuang Luan; Shuang Jin; Bo Yan; Feng Tian (Canadian Journal of Gastroenterology and Hepatology)
Objective. To observe the effects of thalidomide on 2,4,6-trinitrobenzenesulfonic acid- (TNBS-) induced experimental colitis in rats and to explore the possible mechanism of thalidomide in the treatment of CD. Methods. Forty SD rats were randomly assigned into a healthy control group and TNBS-induced colitis groups, including an untreated TNBS-induced colitis group, a low-dose thalidomide group, and a high-dose thalidomide group, with 10 rats in each. After 7 days, the disease activity index (DAI), colon macroscopic damage index (CMDI), and tissue damage index (TDI) were evaluated. The colonic protein and mRNA expression levels of interleukin-6 (IL-6), IL-17, IL-23, and retinoic acid receptor-related orphan nuclear receptor gamma t (RORγt) were determined using immunohistochemistry, western blot, and qRT-PCR. Results. Relative to the untreated TNBS-induced colitis group, the DAI, CMDI, and TDI were all reduced following the administration of thalidomide. Analytical testing (immunohistochemistry, western blot, and qRT-PCR) shows that IL-6, IL-17, IL-23, and RORγt protein and mRNA expression levels were significantly reduced by thalidomide (p<0.05 for all) and that these levels were significantly lower in the high-dose thalidomide group than in the low-dose thalidomide group (p<0.05 for all). Conclusions. Thalidomide effectively alleviated the symptoms and intestinal inflammatory injury induced by TNBS in rats, the effect of which was dose-dependent. The underlying mechanism may be a reduction in the expression levels of IL-6, IL-17, IL-23, and RORγt in colonic tissue and then subsequent inhibition of the differentiation and function of Th17 cells, thus further alleviating the intestinal inflammatory response.